Predictors of achieving remission in schizophrenia patients treated with paliperidone palmitate 3-month formulation - Nash AI (Dove Medical Press, 2019)
Abigail I Nash,1 Ibrahim Turkoz,2 Adam J Savitz,2 Maju Mathews,2 Edward Kim1 1Janssen Scientific Affairs, LLC, Titusville, NJ 08560, USA; 2Janssen Research and Development, LLC, Titusville, NJ 08560, USA Purpose: Long-acting injectable (LAI) antipsychotic paliperidone palmitate 3-month formulation (PP3M) is indicated in the United States for the treatment of schizophrenia only after adequate treatment with paliperidone palmitate 1-month formulation (PP1M) for ≥4 months. This analysis aimed to identify patient and disease characteristics during PP1M treatment associated with greater likelihood of achieving remission after transition to PP3M.Methods: A post hoc analysis of a randomized, Phase III, double-blind, noninferiority trial of PP3M vs PP1M (ClinicalTrials.gov identifier: NCT01515423) was conducted in adult patients with schizophrenia. Patients achieving clinical stability after 17 weeks of open-label PP1M were randomized to 48 weeks of double-blind treatment with PP3M or PP1M. The primary objective of this exploratory post hoc analysis was to identify demographic and/or clinical variables associated with persistent remission after treatment with PP3M. Multiple logistic regression analysis identified the following significant predictors of remission: Positive and Negative Syndrome Scale (PANSS) Marder negative symptom factor score, Clinical Global Impression-Severity (CGI-S) total score, and Personal and Social Performance (PSP) total score.Results: At double-blind baseline, a 1-point reduction in Marder negative symptom factor score was associated with a 20% increase in the odds of achieving remission after PP3M treatment; 1-point reduction in CGI-S was associated with a doubling in remission odds; and 7- and 10-point improvements in PSP scores, respectively, were associated with 42% and 65% increases in remission odds.Conclusion: Patients with early clinically meaningful improvements in disease symptoms and severity while establishing stable PP1M dosage are more likely to achieve remission after transition to PP3M. Keywords: long-acting injectable, symptomatic remission, double-blind treatment